Morphonuclear Relationship Between Prostatic Intraepithelial Neoplasia and Cancers as Assessed by Digital Cell Image Analysis. Issue 5 (28th January 2016) - Petein, Michel; Michel, Patrick; van Velthoven, Roland; Pasteels, Jean-Lambert; Brawer, Michael K.; Davis, John R.; Nagle, Raymond B.; Kiss, Robert
Abstract : Using digital cell image analysis performed on Feulgen-stained nuclei, the nuclear characteristics of prostatic neoplasia, ranging from benign (benign prostatic hyperplasia [BPH]), through dysplastic (prostatic intraepithelial neoplasia [PIN] 1-3), to carcinoma were studied. Four histopathologic groups were studied: group IA (18 samples) contained BPH, PIN 1, and PIN 2 lesions that were from 9 prostate samples free of cancer. Group IB (23 samples) was identical to group IA, contained also BPH, PIN 1, and PIN 2 lesions, but lesions that were from 7 prostate samples where malignant foci were detected elsewhere. Group II (11 samples) were PIN 3 specimens. Group III (24 samples) were carcinomas. Features of neoplastic nuclei were quantified objectively through morphometric (nuclear size), densitometric (nuclear DNA content), and textural (chromatin organization and heterogeneity) parameters. Cell kinetic parameter, i.e., cell pro-liferation index, was assessed from the densitometric measurement. The proliferation index was significantly higher in PIN 3 and cancers as compared to BPH, PIN 1, and PIN 2 tissues. Morphonuclear characteristics were also dramatically distinct among the four groups. Indeed, the nuclear size and the hyperchromatism of severe prostatic dysplasia were similar to those of carcinomas, these two lesion types showing mean parameter values that were higher as compared to BPH, PIN 1, and PIN 2 lesions. Finally, benign tissues related to mild or moderate dysplasia taken in histologic material in which cancer was present already share the morphonuclear characteristics of severe dysplasia, although they are nonproliferating.